Differences In The Severity Of Diabetic Neuropathy Based On Electromyography In Type 2 Diabetes Mellitus Patients With And Without Comorbidities - Dessy Natalia; Maria Belladonna Rahmawati; Maria Immaculata Widiastuti Samekto; Endang Kustiowati; Herlina Suryawati; Elta Diah Pasmanasari (Medica Hospitalia : Journal of Clinical Medicine, 2025)
Introduction: Diabetic neuropathy is one of the most common complications of type 2 Diabetes Mellitus. Hyperglycemia causes axonal abnormalities and impaired schwan cell metabolism. Hypertension and hyperlipidemia associated with atherosclerosis, lipid metabolism and arterial compliance. This study aims to determine the difference in the severity of diabetic neuropathy based on electromyography between type 2 DM patients with and without comorbidities. Methods: This study used a cross sectional design. A total of 78 diabetic neuropathy subjects from Outpatient Installation of Dr. Kariadi Hospital Semarang were divided into 3 groups, 26 subjects without comorbidities, 25 subjects with comorbid hypertension and 27 subjects with comorbid hypertension and hyperlipidemia. Inclusion criteria were aged 40-80 years, distal symmetrical polyneuropathy classification, without comorbid and with comorbid hypertension and hyperlipidemia. Exclusion criteria were patients with chemotherapy, HNP, CKD stage 5, incomplete medical records. Data were analyzed using Kruskal-Wallis comparative test. Results: There is a difference in the severity of diabetic neuropathy based on EMG between type 2 DM patients without comorbidities and with comorbidities (p<0.01). No difference in the severity between patients with type 2 DM without comorbidities and with comorbid hypertension (p 0.058). There is a difference in the severity between patients with type 2 DM without comorbidities and with comorbid hypertension and hyperlipidemia (p<0.01). Conclusion: There is a difference in the severity of diabetic neuropathy based on EMG between patients with type 2 DM without comorbidities, with comorbid hypertension and with comorbid hypertension and hyperlipidemia. The more comorbidities, the greater the severity of diabetic neuropathy.